Sustainable weed management on ornamental beds - Pivetta, K. F L [UNESP]; Rosa, C. S. [UNESP]; Pitelli, R. A. [UNESP]; Romani, G. N. [UNESP]; Batista, G. S. [UNESP]; Mazzini, R. B. [UNESP]; Ferraz, M. V. [UNESP] (My University, 2013)
The weed presence on ornamental beds is a main aspect that interferes with the garden maintenance, especially in tropical countries, as it causes an unpleasant effect and competes with the ornamentals. The use of herbicides is not always economically viable, besides, it causes phytotoxic effects on the ornamental plants, so the alternative to minimize this problem is the use of mulch; however, there is little information on the literature about it. Thus, the aim of this work was to evaluate the effect of rice straw mulching on the weed management of Salvia splendens beds. There were four treatments (0, 4, 6 and 8 t ha-1 of rice straw) and five replications. Brachiaria decumbens (200 plants m-2) and Amaranthus viridis (50 plants m-2) were sown in each plot in order to ensure the weed presence. The evaluation of the weed community was performed 60 days after sowing. The weeds on the plots of 0.48 m2 were identified and removed by hand and then dried in a chamber of forced air ventilation (under 703C) for the dry matter determination which later helped to calculate the phytosociological indexes like the Relative Density, Relative Frequency, Relative Dominance and the Importance Value Index. Nineteen species of weeds were identified. Among them, B. decumbens and A. viridis presented the highest Relative Importance level and the use of 8 t ha-1 of rice straw mulching helped to minimize the Relative Importance of these plants; however, the weed management with the use of rice straw was not effective.
Keywords: Landscaping; Mulching; Rice straw; Salvia splendens